Effects of Particle Surface Charge, Species, Concentration, and Dispersion Method on the Thermal Conductivity of Nanofluids. (6th December 2009) - Gowda, Raghu; Sun, Hongwei; Wang, Pengtao; Charmchi, Majid; Gao, Fan; Gu, Zhiyong; Budhlall, Bridgette
Abstract : The purpose of this experimental study is to evaluate the effects of particle species, surface charge, concentration, preparation technique, and base fluid on thermal transport capability of nanoparticle suspensions (nanofluids). The surface charge was varied by changing the pH value of the fluids. The alumina (Al 2 O 3 ) and copper oxide (CuO) nanoparticles were dispersed in deionized (DI) water and ethylene glycol (EG), respectively. The nanofluids were prepared using both bath-type and probe sonicator under different power inputs. The experimental results were compared with the available experimental data as well as the predicted values obtained from Maxwell effective medium theory. It was found that ethylene glycol is more suitable for nanofluids applications than DI water in terms of thermal conductivity improvement and stability of nanofluids. Surface charge can effectively improve the dispersion of nanoparticles by reducing the (aggregated) particle size in base fluids. A nanofluid with high surface charge (low pH) has a higher thermal conductivity for a similar particle concentration. The sonication also has a significant impact on thermal conductivity enhancement. All these results suggest that the key to the improvement of thermal conductivity of nanofluids is a uniform and stable dispersion of nanoscale particles in a fluid.